2020
DOI: 10.1038/s41467-020-19178-x
|View full text |Cite
|
Sign up to set email alerts
|

Open syntaxin overcomes exocytosis defects of diverse mutants in C. elegans

Abstract: Assembly of SNARE complexes that mediate neurotransmitter release requires opening of a ‘closed’ conformation of UNC-64/syntaxin. Rescue of unc-13/Munc13 mutant phenotypes by overexpressed open UNC-64/syntaxin suggested a specific function of UNC-13/Munc13 in opening UNC-64/ syntaxin. Here, we revisit the effects of open unc-64/syntaxin by generating knockin (KI) worms. The KI animals exhibit enhanced spontaneous and evoked exocytosis compared to WT animals. Unexpectedly, the open syntaxin KI partially suppres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 85 publications
(177 reference statements)
8
38
0
Order By: Relevance
“…Furthermore, one of Munc13’s primary functions is priming the vesicles ( Varoqueaux et al, 2002 ) in addition to templating proper SNARE complex formation for which it assists opening of Munc18-1-bound STX1 ( Ma et al, 2011 ; Ma et al, 2013 ; Lai et al, 2017 ; Wang et al, 2017 ). In this context, it has been shown that STX1A LEOpen recovers neurotransmitter release in Munc13-1/2-deficient mouse or worm neurons albeit only minimally ( Lai et al, 2017 ; Tien et al, 2020 ), while it impairs Munc13’s proper assistance of parallel SNARE complex formation ( Wang et al, 2017 ) and further reduces the locomotor activity and neurotransmitter release in Munc18-1-deficient worms ( Tien et al, 2020 ). Thus, it is plausible that the stability of the SNARE complex is ensured by Munc18-1’s and Munc13’s efficient binding to STX1, which may account for the additive effects of N-peptide deletion and LE Open conformation on the size of RRP ( Figures 4 and 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one of Munc13’s primary functions is priming the vesicles ( Varoqueaux et al, 2002 ) in addition to templating proper SNARE complex formation for which it assists opening of Munc18-1-bound STX1 ( Ma et al, 2011 ; Ma et al, 2013 ; Lai et al, 2017 ; Wang et al, 2017 ). In this context, it has been shown that STX1A LEOpen recovers neurotransmitter release in Munc13-1/2-deficient mouse or worm neurons albeit only minimally ( Lai et al, 2017 ; Tien et al, 2020 ), while it impairs Munc13’s proper assistance of parallel SNARE complex formation ( Wang et al, 2017 ) and further reduces the locomotor activity and neurotransmitter release in Munc18-1-deficient worms ( Tien et al, 2020 ). Thus, it is plausible that the stability of the SNARE complex is ensured by Munc18-1’s and Munc13’s efficient binding to STX1, which may account for the additive effects of N-peptide deletion and LE Open conformation on the size of RRP ( Figures 4 and 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, movement in C. elegans is the outcome of an antagonistic interplay between GABAergic inhibition and cholinergic stimulation [ 103 , 104 ]. The lack of GABAergic input has severe consequence for the movement capacity [ 121 , 122 ], while increased GABAergic stimulation has also been shown to results in cessation of thrashing behavior ([ 33 ]; Fig. 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Release of RIM from Rab3 would allow it to activate Unc13 for Syx1 priming, with open Syx1 engaging Unc18 on a distinct interaction surface that templates the onset of SNARE complex assembly between Syx1 and SV-localized Syb2. Release defects in both Unc10/RIM and Unc13 can be rescued by the open-Syx1 mutation (Tien et al, 2020), consistent with RIM-mediated SV tethering facilitating downstream SNARE-dependent SV priming.…”
Section: Snares Rabs and Rab Effectors Contribute To Target Specificity For Membrane Fusionmentioning
confidence: 58%
“…NSF disassembly of the Tomosyn/t-SNARE complex leads to Unc18 capture of Syx1 for incorporation into productive SNARE complexes (Hatsuzawa et al, 2003;Li Y. et al, 2018). In vivo, tom-1 enhanced release is exaggerated by the open-Syx1 mutation, causing a further increase in tom-1 sensitivity to the acetylcholinesterase inhibitor aldicarb (Tien et al, 2020). Enhanced SV fusion in tom-1 exceeds the residual release in tom-1/unc-13 and tom-1/unc-18 double mutants, indicating Tomosyn also suppresses SNARE assembly within the traditional Unc13/Unc18 priming pathway.…”
Section: Snares Rabs and Rab Effectors Contribute To Target Specificity For Membrane Fusionmentioning
confidence: 99%